Prioritising National Competitiveness over Support for Democracy? Finnish Media Policy in the 21st Century - Ala-fossi Marko; Grönlund Mikko; Hellman Heikki; Lehtisaari Katja; Karppinen Kari; Nieminen Hannu (Centrum Europejskie Uniwersytetu Warszawskiego, 2025)
Ever since the launch of the World Press Freedom Index almost 20 years ago, Finland has always been among the top fi ve countries of that index. According to the annual Reuters Digital News reports, Finnish people also have the highest level of trust in the news media and one of the highest levels of press readership in the EU. Most of the media companies are doing quite well, while Google and Facebook have a much less dominant role in the advertising market than elsewhere in Europe. In this context, you might expect Finland to have a comprehensive and visionary media and communications policy to support democracy. However, our meta-study of Finnish media and communications policy based on two recent reports to the Ministry of Transport and Communications, other earlier studies, along with offi cial documents as well as statistical data suggests that is not the case. Our analysis shows that most decisions have been pragmatic ad hoc solutions serving economic interests rather than any specifi c media and communication policy goals. A closer examination also proves that Finland does not fi t into the Nordic Media Welfare State model either, despite a long, shared history and cultural ties.